Behind Acquisitions of Alliance Partners: Exploratory Learning and Network Embeddedness - Yang, Haibin; Lin, Zhiang (John); Peng, Mike W. (Academy of Management Journal, 2011)
Acquisition research has traditionally been dominated by economic and atomistic assumptions. This study extends acquisition research by integrating behavioral learning and social network perspectives to examine the acquisitions of alliance partners. Specifically, we examine, at the dyadic level, how firms' alliance learning approaches (exploration versus exploitation) and their joint and relative embeddedness in alliance networks (joint brokerage positions and relative centrality) can interact to drive subsequent acquisitions of alliance partners. Our analyses of the U.S. computer industry support our theoretical framework, highlighting the unique and previously underexplored behavioral and relational drivers of acquisitions.